Single stage production of ultra-high-grade iron ore using a novel fluidisation arrangement in a Reflux Classifier - Galvin, Kevin P.; Zhou, James; Rodrigues, Armando F.d.V. (Minerals engineering, 2025)
•A slow rotating rake was introduced into the lower zone of a Reflux Classifier.•The more uniform dense medium led to increased rejection of coarse gangue.•A step change improvement in gravity separation was achieved.•Ultra-high grade iron ore was produced in a single stage separation. The effect of a novel fluidisation arrangement on the gravity separation performance of the Reflux Classifier in upgrading ultrafine iron ore was investigated. A slow-moving rake was used to develop a strong dense medium in the lower zone of the Reflux Classifier, delivering uniform rheology and water fluidisation, and uniform discharge of the underflow product. The feed ore used in the new study, nominally 0–250 μm with Fe grade ∼37 %, was also the subject of a recent investigation (Rodrigues et al, 2024). In the previous work, following extensive optimisation, an Fe product grade of 65.6 ± 0.4 % and Fe recovery of 72.9 ± 0.4 % were achieved. In this new study, involving the new rake, the gravity separation performance improved significantly, eventually achieving an Fe product grade of 68.8 ± 0.4 % Fe and Fe recovery of 72.3 ± 0.4 %. This represented a hematite purity of 98.4 %, with just 1.16 % silica. This work is significant given the production of almost pure hematite in a single stage of physical separation. Further analysis indicated the Ecart Probable Error, Ep, decreased from the previous level of 365 to 244 kg m−3. Samples from the bed profile were analysed to determine the internal system hold-up. The underpinning mechanism responsible for this remarkable separation is discussed.